2022
DOI: 10.3390/nu14071442
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Bovine Milk Exosomes in Metabolic Interorgan Cross-Talk

Abstract: Extracellular vesicles are membrane-enclosed secreted vesicles involved in cell-to-cell communication processes, identified in virtually all body fluids. Among extracellular vesicles, exosomes have gained increasing attention in recent years as they have unique biological origins and deliver different cargos, such as nucleic acids, proteins, and lipids, which might mediate various health processes. In particular, milk-derived exosomes are proposed as bioactive compounds of breast milk, which have been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 234 publications
1
19
1
Order By: Relevance
“…We are very concerned about the recent euphoric promotion of bovine MEX for purposes of human nutrition as well as systemic administration for medical treatments [ 353 , 584 , 585 , 586 , 587 , 588 , 589 ]. In contrast to García-Martínez et al [ 582 ], who praise the generally “beneficial effects” of bovine MEX in metabolic interorgan cross-talk, we only see a meaningful potential use of MEX for infants of mothers who cannot provide adequate breastfeeding and depend on artificial formula administration. We must ask: What happens to the pancreatic β cells when bovine MEX are systemically administered over prolonged treatment periods with the intention to improve other chronic degenerative diseases such as osteoarthritis or osteoporosis [ 590 , 591 , 592 ], chronic inflammatory intestinal diseases [ 593 , 594 , 595 , 596 ], or chronic states of tissue fibrosis [ 597 , 598 ]?…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…We are very concerned about the recent euphoric promotion of bovine MEX for purposes of human nutrition as well as systemic administration for medical treatments [ 353 , 584 , 585 , 586 , 587 , 588 , 589 ]. In contrast to García-Martínez et al [ 582 ], who praise the generally “beneficial effects” of bovine MEX in metabolic interorgan cross-talk, we only see a meaningful potential use of MEX for infants of mothers who cannot provide adequate breastfeeding and depend on artificial formula administration. We must ask: What happens to the pancreatic β cells when bovine MEX are systemically administered over prolonged treatment periods with the intention to improve other chronic degenerative diseases such as osteoarthritis or osteoporosis [ 590 , 591 , 592 ], chronic inflammatory intestinal diseases [ 593 , 594 , 595 , 596 ], or chronic states of tissue fibrosis [ 597 , 598 ]?…”
Section: Discussioncontrasting
confidence: 87%
“…Whereas exosome miR may be valuable tools for the early monitoring of T2DM [ 1 ], the use of bovine MEX for the supposed “improvement of nutrition” and many therapeutic options [ 581 , 582 , 583 , 584 , 585 ], may be another critical experiment on humans, as the operational period of MEX miRs is physiologically restricted to the postnatal period. The artificial use of MEX beyond the period of breastfeeding may turn the highly valuable MEX for the infant [ 14 , 15 , 16 , 17 , 18 , 19 , 586 , 587 , 588 , 589 ] into diabetogenic pathogens in adult life [ 36 , 520 , 521 , 522 , 523 , 524 ].…”
Section: Discussionmentioning
confidence: 99%
“…mEVs have been proved to transfer from milk into the plasma through the intestinal tract of the consuming organism, and to affect gene expression once absorbed by target cells, thereby interfering with the physiological and pathological processes of the consumers [ 22 , 23 , 24 ]. Reif et al reported that mEVs could be absorbed by intestine cells, exerting a therapeutic and anti-inflammatory role in DSS−induced colitis, which involves reducing the expression of IL-6 and TNF-α [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Milk is a known source of exosome-packaged microRNA (dietary miRNAs), small noncoding RNAs containing about 19–22 nucleotides, which negatively regulate the expression of their targeted genes at the post-transcriptional level by driving the degradation of target mRNAs [ 20 , 21 ]. Milk exosomes have attracted considerable attention as a therapeutic approach in different diseased tissues [ 22 ] given their content in bioactive cargos and miRNAs, able to influence different health outcomes [ 23 ]. Exosomal miRNAs are involved in several processes affected by biogenesis and exosome contents and play an important regulatory role in a wide range of biological and pathological pathways, including cancer development [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition alters endogenous miRNA expression, and exogenous functional miRNAs assumed with diet are transferred and bioavailable to organisms [ 26 ]. MiRNAs from cow milk modulate crucial pathways in osteogenesis, nervous, and brain development, as well as regulation of B and T lymphocytes, macrophage activation, and modulation of the adaptative immune response [ 23 ]. Milk-derived miRNAs are also able to prevent the onset of rheumatoid arthritis and to downregulate the expression of several colitis-associated miRNAs, thus improving the macroscopic colitis histopathological scores [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%